2010
DOI: 10.1002/jbmr.142
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibiting activin-A signaling stimulates bone formation and prevents cancer-induced bone destruction in vivo

Abstract: Cancers that grow in bone, such as myeloma and breast cancer metastases, cause devastating osteolytic bone destruction. These cancers hijack bone remodeling by stimulating osteoclastic bone resorption and suppressing bone formation. Currently, treatment is targeted primarily at blocking bone resorption, but this approach has achieved only limited success. Stimulating osteoblastic bone formation to promote repair is a novel alternative approach. We show that a soluble activin receptor type IIA fusion protein (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 52 publications
(56 reference statements)
4
91
1
3
Order By: Relevance
“…Interestingly, neither of these models showed a significant difference in OC number. The anabolic effects of RAP-011 have also been confirmed in mouse models of breast cancer associated-bone disease and osteoporosis [52,93]. A phase I dose-escalation trial in healthy postmenopausal women showed dose-dependent increase in serum levels of bALP, persisting up to 120 days after a single intravenous injection of 3-mg/kg.…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 89%
See 3 more Smart Citations
“…Interestingly, neither of these models showed a significant difference in OC number. The anabolic effects of RAP-011 have also been confirmed in mouse models of breast cancer associated-bone disease and osteoporosis [52,93]. A phase I dose-escalation trial in healthy postmenopausal women showed dose-dependent increase in serum levels of bALP, persisting up to 120 days after a single intravenous injection of 3-mg/kg.…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 89%
“…Compared with vehicle, RAP-011 increased OB number, bone surface occupied by OB and mineralization. Again RAP-011 yielded a 41% reduction in serum paraprotein levels and a 37% reduction in the tumor burden of bone [52]. Interestingly, neither of these models showed a significant difference in OC number.…”
Section: Treatment Of MM Bone Disease With Bone-anabolic Agentsmentioning
confidence: 93%
See 2 more Smart Citations
“…[80] Activin A levels were increased in bone marrow plasma of myeloma patients with osteolytic disease and has been proposed to play an important role in myeloma bone disease, at least in part by inhibiting phosphorylation of SMAD1/5/8 during osteoblastogenesis. [81,82] Lenalidomide treatment has been shown to cause activin A secretion by myeloma BMSC, providing a rationale for a combination treatment of lenalidomide with activin A inhibition. [83] TGF-β is abundant in the bone marrow of myeloma patients, and represses bone formation in osteolytic lesions.…”
Section: Bmp and Bone Disease In Multiple Myelomamentioning
confidence: 99%